Designing A Web-Based E-Module for Empowering Tenth-Grade Students' Writing Skills on Descriptive Text - Marsya Nanda Dian Agustina; Miza Rahmatika Aini; Hesty Puspitasari (International Journal of Educational Development, 2026)
The study titled “Designing a Web-Based E-Module for Empowering Tenth-Grade Students’ Writing Skills in Descriptive Text” aims to develop a digital learning medium to improve students’ descriptive writing abilities. The research applies a Design and Development (D&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation, supported by a descriptive quantitative method. The study addresses limitations of traditional, teacher-centered instruction that relies heavily on printed materials by integrating technology into the learning process. The research begins with an analysis of existing teaching practices and learning resources for descriptive text writing. Based on this analysis, a web-based e-module is designed to provide a more interactive and engaging learning experience. The module includes structured materials such as definitions, purposes, text structures, language features, examples, and practice exercises. The e-module is then implemented in a tenth-grade classroom setting, followed by an evaluation of its effectiveness using quantitative data. The results indicate that the web-based e-module effectively improves students’ descriptive writing skills. Interactive features, including multimedia content, self-paced activities, and immediate feedback, enhance students’ motivation and active participation. Teachers and students report positive perceptions regarding the practicality, accessibility, and usefulness of the e-module. Pre-test and post-test results also show a clear improvement in students’ writing performance. Overall, the study concludes that web-based e-modules are a promising instructional medium for enhancing writing skills and supporting student-centered, technology-integrated English language learning.